Yellow fever disease severity and endothelial dysfunction are associated with elevated serum levels of viral NS1 protein and syndecan-1Research in context - Francielle T.G. de Sousa; Colin M. Warnes; Erika R. Manuli; Laurentia V. Tjang; Pedro H. Carneiro; Luzia Maria de Oliveira Pinto; Arash Ng; Samhita Bhat; Jose Victor Zambrana; Luiz G.F.A.B. D’Elia Zanella; Yeh-Li Ho; Camila M. Romano; et al. (EBioMedicine)
Summary: Background: Yellow fever virus (YFV) infections are a major global disease concern with high mortality in humans, and as such it is critical to identify clinical correlates of disease severity. While nonstructural protein 1 (NS1) of the related dengue virus is implicated in contributing to vascular leak, little is known about the role of YFV NS1 in severe YF and mechanisms of vascular dysfunction in YFV infections. Methods: Using serum samples from laboratory-confirmed YF patients with severe (n = 39) or non-severe (n = 18) disease in a well-defined hospital observational cohort in Brazil, plus samples from healthy uninfected controls (n = 11), we investigated factors associated with disease severity and endothelial dysfunction. Findings: We found significantly increased levels of NS1, as well as syndecan-1, a marker of vascular leak, in serum from severe YF as compared to non-severe YF or control groups. We also showed that hyperpermeability of endothelial cell monolayers treated with serum from severe YF patients was significantly higher compared to non-severe YF and control groups, as measured by transendothelial electrical resistance (TEER). Further, we demonstrated that YFV NS1 induces shedding of syndecan-1 from the surface of human endothelial cells. Notably, YFV NS1 serum levels significantly correlated with syndecan-1 serum levels, TEER values, and signs of disease severity. Syndecan-1 levels also significantly correlated with clinical laboratory parameters of disease severity, viral load, hospitalization, and death. Interpretation: This study provides further evidence for endothelial dysfunction as a mechanism of YF pathogenesis in humans and suggests serum quantification of YFV NS1 and syndecan-1 as valuable tools for disease diagnosis and/or prognosis. Funding: This work was supported by the US NIH and FAPESP.